U.S. Army human intelligence collector field manual (Lyons Press, 2014)
Issued by the Department of the Army, this manual gives instructions on the structure, planning and management of human intelligence operations, the debriefing of soldiers, and the analysis of known relationships and map data. The largest and most updated section of the document details procedures for the screening and interrogation of prisoners of war and unlawful combatants, all of which was revised after the water-boarding controversy.